Pengaruh Manajemen Sumber Daya Manusia Terhadap Kinerja Karyawan Pada PTPN 3 Sei Batang Hari Medan - Miranda Fahriani; Khairuddin Lubis; Yurmaini Yus (AKUNTANSI 45, 2023)
This study aims to know "The Impact of Human Resource Management on Employee Performance in PTPN III, SEI BATANG HARI, MEDAN". This research is quantitative and uses primary data through the dissemination of questionnaires to employees of PTPN III, Sei Batang Hari, Medan, with a total of 115.618 employees. It consists of 6,264 senior executives and 109,354 executive employees. The sampling technique uses purposive random sampling, i.e., sample collection, in which case the researcher determines the boundaries of the subjects used as sample research, and the sample used is a total of 30 respondents. Data is processed through the SPSS 20.0 program with a simple linear regression analysis technique. The results of the study show that there is a significant impact of human resource management on the performance of employees on the PTPN 3 Sei Batang Day Field. The R-squared regression test yielded a result of 0.346, which means that the X variable can only influence the Y variable by 34.6%, with the remaining 65.4% being influenced by other variables outside the study. The t (partial) test of 0,001 is smaller than 0,05. Thus, the hypothesis that human resource management has a significant impact on employee performance is acceptable.